Tensile bond strength of facial silicone and acrylic resin using different primers - Sasiwimol Sanohkan; Boonlert Kukiattrakoon; Chaimongkon Peampring (Wolters Kluwer Medknow Publications, 2017)
Aim: To evaluate the tensile bond strength between Silastic MDX 4-4210 silicone and autopolymerizing acrylic resin (Orthojet) with two facial silicone primers (A306 and A330-G) and three primers used for silicone-based intraoral reliner materials [Sofreliner tough primer (ST); Mucosoft bond liner primer (ML); and Mucopren adhesive (MA)]. Materials and Methods: Sixty specimens were divided into six groups according to the primers used to attach the facial silicone to the acrylic resin. All specimens were loaded in tension mode in a universal testing machine with a crosshead speed of 10 mm/min until bonding failure occurred. Results: The highest bond strength values were found in the ST group (1.42 ± 0.24 MPa) followed by the MA group (1.39 ± 0.20 MPa) and the ML group (1.32 ± 0.24 MPa), which were significantly different from the A330-G group (1.12 ± 0.10 MPa), A306 group (0.69 ± 0.0.11 MPa), and the control group (0.18 ± 0.08 MPa). The mode of failure for all specimens was found to be adhesive failure at the facial silicone and bonding agent interface. Conclusion: This study suggests that silicone-based intraoral reliner materials can be used as facial silicone primers.